Penerapan Pendekatan Kontruktivis Sosial (Social Constructivist Approaches) dalam Meningkatkan Motivasi, Pemahaman, dan Prestasi Belajar Siswa - Masithoh Al Hamizah; Shalih Husni (Fak. Tarbiyah UIN Maliki Malang, 2011)
Islamic religious education is a conscious and deliberate effort in preparing learners to recognize, understand, to live up to believe in the teachings of Islam coupled with guidance to respect other faiths in conjunction with the harmony between religious believers to manifest the unity and the unity of the nation. Scaffolding is a technique to alter the level of support. During the teaching session, someone more expert (teacher, or students who are better able to) adjust the amount of guidance to the level of student performance that has been achieved. In this study the research methods used type class action (action research) with the object of research is a class X student of SMAN 1 Malang. For random sampling technique used by the sample of 35 students. After the data is collected, then the processing performed using SPSS version 16. The results showed that the use scaffolding method can improve the achievement and student understanding. In the first cycle the average value of class X subjects PAI II 71 and the cycle increased to 77 with a significance level of 0000 and the third cycle of student scores to 83.